IL-10 blocks the development of resistance to re-infection with Schistosoma mansoni. - Mark S Wilson; Allen W Cheever; Sandra D White; Robert W Thompson; Thomas A Wynn (PLoS Pathogens)
Despite effective chemotherapy to treat schistosome infections, re-infection rates are extremely high. Resistance to reinfection can develop, however it typically takes several years following numerous rounds of treatment and re-infection, and often develops in only a small cohort of individuals. Using a well-established and highly permissive mouse model, we investigated whether immunoregulatory mechanisms influence the development of resistance. Following Praziquantel (PZQ) treatment of S. mansoni infected mice we observed a significant and mixed anti-worm response, characterized by Th1, Th2 and Th17 responses. Despite the elevated anti-worm response in PBMC's, liver, spleen and mesenteric lymph nodes, this did not confer any protection from a secondary challenge infection. Because a significant increase in IL-10-producing CD4(+)CD44(+)CD25(+)GITR(+) lymphocytes was observed, we hypothesised that IL-10 was obstructing the development of resistance. Blockade of IL-10 combined with PZQ treatment afforded a greater than 50% reduction in parasite establishment during reinfection, compared to PZQ treatment alone, indicating that IL-10 obstructs the development of acquired resistance. Markedly enhanced Th1, Th2 and Th17 responses, worm-specific IgG1, IgG2b and IgE and circulating eosinophils characterized the protection. This study demonstrates that blocking IL-10 signalling during PZQ treatment can facilitate the development of protective immunity and provide a highly effective strategy to protect against reinfection with S. mansoni.